2016
DOI: 10.3390/ijms17091459
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNAs: A Next-Generation Clinical Biomarker for Digestive System Cancers

Abstract: MicroRNAs (miRNAs) are short noncoding RNAs that post-transcriptionally regulate gene expression and play important roles in various physiological and developmental processes such as oncogenic or tumor suppressive regulators. Specific miRNA expression signatures have been identified in a number of human cancers. Cell-free miRNAs have recently been stably detected in plasma and serum (circulating miRNAs), and their presence in blood has attracted the attention of researchers due to their potential as non-invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 90 publications
0
49
0
1
Order By: Relevance
“…Numerous circulating miRNAs have been identified as potential biomarkers of various cancer types 16,19,25,39,[53][54][55] . Regarding PCa, to date, more than thirty miRNAs have been reported as potentially useful biomarkers 31,33,37,[56][57][58][59] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous circulating miRNAs have been identified as potential biomarkers of various cancer types 16,19,25,39,[53][54][55] . Regarding PCa, to date, more than thirty miRNAs have been reported as potentially useful biomarkers 31,33,37,[56][57][58][59] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some extracellular miRNAs occur not only through cell lysis but also through active secretion [25][26][27] and can function as intercellular transmitters 19,26,28,29 . Thus, various blood-based miRNAs have been identified, including those in this study, and can be used for cancer detection, monitoring tumor dynamics, and predicting prognosis and chemoresistance [30][31][32][33][34][35][36][37][38][39][40][41][42] . Recently, Kosaka and Ochiya et al suggested a novel mechanism -that miRNAs could facilitate the system of maintenance and surveillance against cancer progression.…”
mentioning
confidence: 99%
“…The epigenetic involvement of SST gene silencing in CRC is supported by observations that SST methylation levels in tumor tissues are significantly higher than that in adjacent normal mucosa of CRC patients or normal mucosa from healthy controls (44) and that hypermethylation was found in percentages ranging from 88% to 100% in primary tumours (42,44). (47).…”
Section: Prognostic Role Of Circulating Biomarkersmentioning
confidence: 92%
“…As indicated by the usefulness of cell-free DNA and circulating tumor cells, the concept of "liquid biopsy" through circulating miRNAs may also provide ideal individualized therapeutic strategies for cancer patients and contribute to the development of precision medicine. Indeed, previous studies, including our own, have identified various blood-based miRNA biomarker candidates, which are useful for cancer detection, monitoring tumor dynamics, and predicting malignant potential, prognosis, and chemoresistance in cancer patients [32][33][34][35][36][37][38][39][40][41][42][43][44][45] .…”
Section: Circulating Micrornas Are a Promising Source Of Diagnostic Amentioning
confidence: 99%